Conjugation of polycationic peptides extends the efficacy spectrum of β-lactam antibiotics - Werner, Julia; Umstätter, Florian; Böhmann, Manuel Ben; Müller, Hannah; Beijer, Barbro; Hertlein, Tobias; Kaschnitz, Laura; Bram, Veronika; Kleist, Christian; Klika, Karel D.; Mühlberg, Eric; Braune, Gabriel; et al. (Advanced science, 2024)
Antibiotic-resistant enterococci represent a significant global health challenge. Unfortunately, most β-lactam antibiotics are not applicable for enterococcal infections due to intrinsic resistance. To extend their antimicrobial spectrum, polycationic peptides are conjugated to examples from each of the four classes of β-lactam antibiotics. Remarkably, the β-lactam-peptide conjugates gained an up to 1000-fold increase in antimicrobial activity against vancomycin-susceptible and vancomycin-resistant enterococci. Even against β-lactam-resistant Gram-negative strains, the conjugates are found to be effective despite their size exceeding the exclusion volume of porins. The extraordinary gain of activity can be explained by an altered mode of killing. Of note, the conjugates showed a concentration-dependent activity in contrast to the parent β-lactam antibiotics that exhibited a time-dependent mode of action. In comparison to the parent β-lactams, the conjugates showed altered affinities to the penicillin-binding proteins. Furthermore, it is found that peptide conjugation also resulted in a different elimination route of the compounds when administered to rodents. In mice systemically infected with vancomycin-resistant enterococci, treatment with a β-lactam-peptide conjugate reduced bacterial burden in the liver compared to its originator. Therefore, peptide modification of β-lactam antibiotics represents a promising platform strategy to broaden their efficacy spectrum, particularly against enterococci.